Learning Evaluation Through the Safe Exam Browser App - Husni, Muhammad Gosani; Ali, Mohammad (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2024)
Every implementation of learning evaluation will have problems that arise so that innovations are needed that can overcome these problems. One of the innovations made to facilitate the learning evaluation system, so that learning evaluation activities will be helped. The research method used by researchers is qualitative, which refers to web data and observation results with interviews. So as to find how the effectiveness in implementing learning evaluation using Safe Exam Browser, then some of the supporting and inhibiting factors that are felt when using the application. By conducting considerations and discussions, the researcher concluded that using the Safe Exam Browser (SEB) application is very effective for modern-based educational institutions, with adequate media this application is very supportive to produce maximum Learning Evaluation, because the researcher mentioned that there are two values contained in it, namely the value of honesty and the value of self-confidence. With these two values, students will have good character and can have high morality for long-term provision for future success. The hope of the researcher is that the Safe Exam Browser application can be updated even better so that many institutions use the application, it will increase the value of higher quality and more advanced education.